2019
DOI: 10.1182/bloodadvances.2019000574
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia–induced T-cell suppression can be reversed by inhibition of the MAPK pathway

Abstract: Key Points MEK inhibition rescues T cells from activation-induced cell death in an AML model. MEK inhibitor sensitivity is associated with inflammation pathways and PD-L1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…More recent evidence shows that high expression of PD-L1 on AML cells is associated with worse overall survival in patients with FLT3-ITD and NPM1 mutations [ 60 ]. Several studies highlighted induction of PD-L1 expression after treatment with interferons [ 61 , 62 ], while reduced expression of PD-L1 was observed on AML cells in patients after treatment with mitogen activated protein kinase kinase (MEK) inhibitors [ 61 , 63 ]. Additionally, signal transducer and activator of transcription 3 (STAT3) inhibition in AML mouse model resulted in downregulation of PD-L1 and induction of anti-leukemic immune response [ 64 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%
“…More recent evidence shows that high expression of PD-L1 on AML cells is associated with worse overall survival in patients with FLT3-ITD and NPM1 mutations [ 60 ]. Several studies highlighted induction of PD-L1 expression after treatment with interferons [ 61 , 62 ], while reduced expression of PD-L1 was observed on AML cells in patients after treatment with mitogen activated protein kinase kinase (MEK) inhibitors [ 61 , 63 ]. Additionally, signal transducer and activator of transcription 3 (STAT3) inhibition in AML mouse model resulted in downregulation of PD-L1 and induction of anti-leukemic immune response [ 64 ].…”
Section: Leukemia-derived Factors That Promote Immune Evasionmentioning
confidence: 99%
“…We previously showed that our genetically-engineered mouse model, FLT3-ITD +/- TET2 flox/+ LysM-Cre +/- displays a profound defect in T cell proliferative capacity 44 . To further characterize the tumor microenvironment and functional capacity of T cells derived from this mouse model, we performed multi-color flow cytometry to immunophenotype myeloid and lymphoid population and histology of multiple organ sites.…”
Section: Resultsmentioning
confidence: 89%
“…CREB binding protein (CREBBP) is an important protein for the autonomous cellular regulation of hematopoiesis, including the stem cell [ 71 ]. For example, it is known that the bone marrow microenvironment is suppressive for the active cells of the immune system, therefore promoting the leukemic clone progression [ 72 , 73 , 74 ]. Regulatory T-cells have been identified for being used by leukemic cells to evade the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory T-cells have been identified for being used by leukemic cells to evade the immune response. In addition, the protective effects of the marrow achieve protection against cytotoxic drugs, allowing the development of cell resistance that imposes the need for the development of appropriate drugs and the microenvironment [ 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%